Die navorsingsmetode van die fundamentele opvoedkunde* - Walt, J. L. Van der (Koers, 1982)
Fundamental Pedagogics, as one of the group of sciences constituting Education, has it's own set of research methods, although investigation of and thought about these do not always seem to he firmly grounded. Such investigation reveals that the inductive, verification o f hypothesis method as well as the method of literature study, is a basic method of this discipline. Apart from these well-known methods there are, however, other methods of research which are useful only for Fundamental Pedagogics. Such methods would include the method of reflection about principles where the process of thinking fulfils itself within the framework of regulative principles; the method of the analysis of phenomena as a subsection of the encompassing method of the empirical study of structure, the transcendental-critical method with its various phases (the immanent. the transcendental, the. transcendent and the ethretical) and the problem- historical method. For the Fundamental Pedagogics student all these methods (as far as possible in combination to evade the danger of monism) are useful and important, because they do not only enable him to analyse the phenomenon of education, hut also to reflet tellingly on educational events and to describe educational structures, as well as to dele) mine which religion is the driving force behind a specific theory of education and practice of education, and which then functions within that framework.